Examining the level of metacognitive obsessive, intellectual-practical beliefs in the COVID-19 epidemic: Examining the level of metacognitive obsessive, intellectual-practical beliefs in the COVID-19 epidemic - jafari, Mahnaz; eil, Soheil; Hamidi, Masoumeh; Sobhanian, Saeed; Sadeghi Mazzee, Safoori (Shahroud Journal of Medical Sciences, 2023)
Introduction: Currently, the world community is experiencing one of the biggest health crises in recent decades. The psychological consequences of Corona can include a range of feelings of loneliness, boredom and aggressiveness to anxiety and mental distress. Therefore, this study was conducted with the aim of investigating the level of obsessive and practical metacognitive beliefs in the COVID-19 pandemic.Materials and methods: This descriptive-analytical study was conducted cross-sectionally on 416 people who referred to corona testing centers using available sampling method. The data was collected using three depression, anxiety and obsession, intellectual-practical questionnaires, after collecting the data, it was entered into SPSS 18 and analyzed with the help of descriptive and analytical statistics.Findings: The results of this study showed that 61% of the participants had moderate anxiety, 20% had moderate depression, and the mean obsessive-compulsive score was 68.9 ± 19.8. The results of linear regression also showed that depression can predict the occurrence of practical obsessions.Conclusion: The results of the present study showed that people with obsessive-compulsive disorder were greatly affected during the COVID-19 pandemic. And anxiety is a common disorder among those who refer to corona testing centers in Shiraz city, and more than half of those who refer to these centers are suffering from anxiety disorder.